Survival of larvae of Anoplognathus porosus (Dalman) and Sericesthis nigrolineata Boisd. (Coleoptera: Scarabaeidae) - Syed Hassan, Syed Tajuddin; Hilditch, J. A. (British Ecological Society, 1976)
In the New England Tablelands of New South Wales in Australia, the population densities of pasture scarab fluctuate widely from year to year, and damage varies from negligible to complete destruction of pastures. There is a need to predict the time, place and size of these outbreaks in order that control measures may be implemented only when and where necessary. A systems approach to the scarab problem has been suggested (Davidson, - Wiseman & Wolfe 1970),based on the construction of simulation models for each stage of the life cycle, which are validated separately in implanted field populations. Under field conditions in New England, high mortality of the larvae of Sericesthis nigrolineata Boisd. occurs in the first instar (T. J. Ridsdill Smith, personal communica- tion). Laboratory studies have shown that high temperatures and extremes of soil moisture can explain much of this mortality (Davidson, Wiseman & Wolfe 1972a, b). A similar investigation of the responses of Anoplognathus porosus (Dalman) has shown that its larvae are more tolerant of high temperatures (Hassan 1975). Using the field plot layout of semi-controlled environments developed by Davidson et al. (1970) to validate simulation models for larvae, the survival of Sericesthis nigro- lineata and Anoplognathus porosus larvae was compared.